TRADITIONAL HERBAL MEDICINAL PLANT TRIGONELLA FOENUM-GRAECUM; PHARMACOLOGICAL SIGNIFICANCE: A REVIEW - Rohit K; Shreya A; Surender G; Astik K; Shubham S; Mukesh S; Bhairvi K (Journal of Biomedical and Pharmaceutical Research, 2020)
Fenugreek is the traditional herbal medicinal plant which is most widely use in many pharmaceutical medicinal preparation as well as food supplements. Haebal preparation and plants play an important role for human health. Fenugreek plant, seeds and its leaf contain a wide verity of flavonoids like Quercetin, rutin, vetexin, saponins like gracecunins, fenugrin B, fenugreekine, amino acids like isoleucine, 4- hydroxyisoleucine, histidine, leucine, lysine, Alkaloid like trigonellin, Fenugreek also contain mucilage. Fenugreek verity Trigonella foenum- graecum show many pharmacological and therapeutic action like anti- inflammatory, stomachic, Diuretic, Carminative, Anaesthetic, Stimulant, Anti-diabetic Analgesic, Nephroprotective, Neuroprotective, Hair Tonic, Expectorent, Demulcent, Blood purifier, General body tonic, Aphrodisiac, Anti- bacterial, Anti-oxidant, Anti-fungal, Anti-hyperlipidemic, anti- cancerous activity.